The Effect of Transformational Leadership, Work Environment, and Life-Work Balance on Employee Job Satisfaction in the Manufacturing Industry in Surabaya Region - Suhara, Ade; Mayasari, Nanny; Dinarwati , Sri; Suhendra, Agus; Talindong, Agustinus (West Science Business and Management, 2024)
This study investigates the influence of transformational leadership, work environment, and work-life balance on employee job satisfaction within the manufacturing industry in the Surabaya region. A quantitative research design employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was utilized to analyze data collected from 160 employees across various manufacturing sectors. The findings reveal significant positive relationships between transformational leadership, work environment, work-life balance, and employee job satisfaction. Transformational leadership emerged as a key predictor of employee job satisfaction, emphasizing the importance of visionary leadership in fostering a positive work culture. Additionally, a supportive work environment and satisfactory work-life balance were found to significantly impact employee satisfaction. These findings underscore the interconnectedness of organizational factors in shaping employee perceptions and experiences within the manufacturing industry. The study contributes to both theoretical understanding and practical implications for organizational management and human resource practices, providing insights for enhancing employee satisfaction and organizational success in the Surabaya manufacturing context.